1975
DOI: 10.1037/0021-843x.84.4.386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of marijuana on divergent and convergent production cognitive tests.

Abstract: In a study of the effects of cannabis on cognitive functioning, several cognitive and psychomotor tests were administered to four groups of subjects: (a) a high-dose group (equivalent to 6 mg of A° THC), (b) a low-dose group (equivalent to 3 mg of A" THC), (c) a placebo group, and (d) a control group. Cannabis was smoked in the form of marijuana. Even the subjects who received the low dose showed impairment on the Wechsler Adult Intelligence Scale Block Design Test and Memory-for-Designs Test. The high-dose su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Unfortunately, the available research on the link between cannabis and creativity allows only for partial verification of these expectations. With respect to divergent thinking, one study showed that subjects intoxicated with joints (cannabis cigarettes) containing a low dose of THC (3 mg in total) displayed significantly enhanced performance on two divergent production tasks, compared to a group that received a higher THC dose (6 mg in total; Weckowicz et al 1975 ). Curran et al ( 2002 ) showed that, as compared to placebo, oral THC (7.5 and 15 mg) dose-dependently improved verbal fluency—an important aspect of divergent thinking (Guilford 1967 ), at least as assessed by the AUT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the available research on the link between cannabis and creativity allows only for partial verification of these expectations. With respect to divergent thinking, one study showed that subjects intoxicated with joints (cannabis cigarettes) containing a low dose of THC (3 mg in total) displayed significantly enhanced performance on two divergent production tasks, compared to a group that received a higher THC dose (6 mg in total; Weckowicz et al 1975 ). Curran et al ( 2002 ) showed that, as compared to placebo, oral THC (7.5 and 15 mg) dose-dependently improved verbal fluency—an important aspect of divergent thinking (Guilford 1967 ), at least as assessed by the AUT.…”
Section: Introductionmentioning
confidence: 99%
“…For convergent thinking, the evidence is even more limited. Weckowicz et al ( 1975 ) observed a trend toward less efficient convergent thinking task after smoking joints containing a low dose of THC (3 mg in total) or a higher dose (6 mg in total), in comparison to both a placebo and a pure control group. However, the same study also found impaired convergent thinking but only for the high-dose condition.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this test doesn't contain an unique score but several quotations by life periods. Regarding to the studies investigating cognitive disorders in cannabis users (between 10 to 44 subjects) [25][26][27][30][31][32][33][34][35][36][37][38][39] and regarding to a meta-analysis of works concerning overgeneralization of autobiographical events (between 12 to 37 subjects, excepted one study with 93 subjects in the experimental group but only 24 subjects in the control group) [40], we decided to include 30 cannabis users and 30 non-users subjects. Moreover, Potheegadoo et al explore AM impairments in patients suffering from schizophrenia and they include 25 patients and 25 control subjects [41].…”
Section: Participantsmentioning
confidence: 99%
“…While Crawford didn't examine creative processes per se, it can be predicted, on the basis of the hypnotic-related studies reported earlier, that such a relationship would be found. More direct evidence can be extracted from a study by Weckowicz, Fedora, Mason, Radstaak, Bay and Yonge (1975). These investigators administered a battery of tests to groups of subjects who differed in the amount of marijuana they had ingested.…”
mentioning
confidence: 99%
“…While this basic design has been employed in some related studies (e.g., Harshman, et aI., 1976) it has yet to be used in studies of creativity, although R. C. Gur and Rayner (1976) do approach it. The relevance of predicting a pattern of results cannot be overemphasized since a general facilitation or inhibition of scores due to an experimental manipulation provides no support for the hypothesis that the right hemisphere selectively enhances creative production but may just indicate fatigue, heightened attention, fear or any of a number of nonspe- It was precisely on these grounds that the Weckowicz, et al (1975) data was deemed inadequate support for a hemispheric interpretation. Even if the predicted pattern of results outlined above are found, a right hemispheric interpretation of the data has not been necessarily proven.…”
mentioning
confidence: 99%